Cooling down AI regulation controversies: Three closure processes in the Chilean legislative arena - Mónica Humeres; Dusan Cotoras; Renato Moretti; Iñaki Oyarzún-Merino; Teresa Correa; Claudia López (Big Data & Society)
According to social studies of artificial intelligence (AI), public AI controversies tend to dissipate relatively quickly despite well-documented risks and harms. The reasons for this lack of controversiality are beginning to be studied. Drawing on the framework of sociotechnical controversies, we analyze the de-escalation of contentious discussions observed in the AI legislative process by Chile's National Congress. Utilizing a qualitative approach, we tracked the deliberations hosted by the Chamber of Deputies and the Senate of Chile across 51 sessions between 2023 and 2024. We describe three processes of cooling down in the AI debates: (1) deflection of technology liability, (2) instrumentalization of technology policy, and (3) moralization of technology use. However, constructive exchanges appear in some circumstances, which allow us to foresee some favorable conditions for participation in the debates on AI regulation. This paper contributes to AI controversy studies by outlining cooling-down processes and conditions that foster dialogue and providing a critical perspective on the formation of AI regulation.